2002
DOI: 10.1021/ja012036c
|View full text |Cite
|
Sign up to set email alerts
|

Acetate Binding at the Photosystem II Oxygen Evolving Complex:  An S2-State Multiline Signal ESEEM Study

Abstract: Previously, using acetate deuterated in the methyl hydrogen positions, we showed that acetate binds in close proximity to the Mn cluster/Y(.)(z) tyrosine dual spin complex in acetate-inhibited photosystem II (PSII) preparations exhibiting the "split" EPR signal arising from the S(2)-Y(.)(z) interaction [Force, D. A.; Randall, D. W.; Britt, R. D. Biochemistry 1997, 36, 12062-12070]. By using paramagnetic NO to quench the paramagnetism of Y(.)(z), we are able to observe the ESEEM spectrum of deuterated acetate i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
45
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 85 publications
(302 reference statements)
4
45
0
Order By: Relevance
“…However, they did not provide any information about the number and location of Cl Ϫ ions within the OEC. The inhibition of particular S-state transitions upon depletion of Cl Ϫ has been taken as evidence of the close proximity of Cl Ϫ to the Mn 4 Ca cluster, a proximity that also was suggested by studies of electron spin echo envelope modulation (19,20) and Fourier transform infrared spectroscopic studies (21). Recent EXAFS studies, however, suggested that Cl Ϫ ions do not bind to the Mn 4 Ca cluster in its S 1 state, and that no Cl Ϫ is present within a distance of 5 Å from the metal center (13).…”
mentioning
confidence: 86%
“…However, they did not provide any information about the number and location of Cl Ϫ ions within the OEC. The inhibition of particular S-state transitions upon depletion of Cl Ϫ has been taken as evidence of the close proximity of Cl Ϫ to the Mn 4 Ca cluster, a proximity that also was suggested by studies of electron spin echo envelope modulation (19,20) and Fourier transform infrared spectroscopic studies (21). Recent EXAFS studies, however, suggested that Cl Ϫ ions do not bind to the Mn 4 Ca cluster in its S 1 state, and that no Cl Ϫ is present within a distance of 5 Å from the metal center (13).…”
mentioning
confidence: 86%
“…Much research effort has been focused on obtaining ESEEM and ENDOR spectra of the various states of PSII [67][68][69][70][71][72][73][74][75]. While the Mn(II) oxidation state is likely not accessed during any of the so-called S states of the water oxidation reaction2 [76,77], Mn(II) ions are necessary for the in vivo photoassembly of the Mn cluster [78].…”
Section: Past Studiesmentioning
confidence: 99%
“…These include (1) oxalate oxidase, which catalyzes the conversion of oxalate and oxygen into hydrogen peroxide and carbon dioxide (Requena and Bornemann, 1999); (2) the Mn-containing superoxide dismutase, located in the mitochondria, which protects the tissue from oxidative stress (Bowler et al, 1991;Alscher et al, 2002); and (3) the oxygen-evolving complex of PSII (Britt, 1996;Clemens et al, 2002;Rutherford and Boussac, 2004). In addition, Mn is an unspecific activator of a number of different enzymes, such as decarboxylases and dehydrogenases in the tricarboxylic acid cycle, Phe ammonia-lyase in the shikimic acid pathway, and in several glycosyltransferases in the Golgi apparatus (Marschner, 1995;Nunan and Scheller, 2003).…”
mentioning
confidence: 99%